Pengaruh Permainan Edukatif Dalam Meningkatkan Stimulasi Otak Pada Fase Golden Age Di TK PGRI At-Taqwa - Amelia Putri, Annisa; Hasanah, Dinda Lutfi; Hasanah, Hilmiatun; Jevanesia, Nawa Fisca; Zahra, Septiani; Nurpatonah, Dini; Firmansyah, Andan (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: Stimulation is any activity that involves a child's fine motor and cognitive abilities. In optimizing children's brain development according to their age stages, especially in the golden age phase. One educational tool that can be used is puzzle games. Objective: Knowing the effectiveness of puzzle games as a counseling medium to increase brain stimulation in children at Pgri At-Taqwa Kindergarten. Method: The model used in this research in the form of community service is health education with the concept of play. In this counseling, participants are expected to be able to carry out it comprehensively, especially in creating new behavior regarding stimulating children's brain development with puzzle media. Result: Based on initial test results, it is known that around 70% of children can complete the puzzle, while 30% of children are still unable to complete the puzzle so they still need help from other people. These results indicate that students' cognitive abilities have not yet been partially achieved. Conclusion: The conclusion from the implementation of this community service is that counseling in stimulating brain development using puzzle media has a positive effect. The children seemed enthusiastic and active participants in taking part in the activity.